2020
DOI: 10.1038/s41598-020-63546-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new intraocular lens power calculation method based on lens position estimated with optical coherence tomography

Abstract: A new method is developed and validated for intraocular lens (IOL) power calculation based on paraxial ray tracing of the postoperative IOL positions, which are obtained with the use of anterior segment optical coherence tomography. Of the 474 eyes studied, 137 and 337 were grouped into training and validation sets, respectively. The positions of the implanted IOLs of the training datasets were characterized with multiple linear regression analyses one month after the operations. A new regression formula was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
2
14
0
Order By: Relevance
“…The current study compared the accuracy of conventional IOL power calculation formulas with that of ML-based methods in predicting postoperative refraction. The absolute prediction errors of the conventional formulas were nearly the same as those of previous reports [ 3 , 4 , 5 ]. In addition, the Barrett Universal II formula had low prediction error, which is in accordance with previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The current study compared the accuracy of conventional IOL power calculation formulas with that of ML-based methods in predicting postoperative refraction. The absolute prediction errors of the conventional formulas were nearly the same as those of previous reports [ 3 , 4 , 5 ]. In addition, the Barrett Universal II formula had low prediction error, which is in accordance with previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Future studies are needed, such as using data from other races. Alternatively, the newly proposed formula using AS-OCT by Satou et al that is independent of ocular axial length may be optimal [ 4 ]. However, it is complicated to obtain detailed AS-OCT data accurately from all preoperative cataract patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are usually based on the parameters of optical coherence tomography, biometry, and anterior segment optical coherence tomography acquired before and after cataract surgery. 14,[28][29][30] In a work evaluating the prediction accuracy of ELP after cataract surgery using a multiobjective evolutionary algorithm, 31 the ELP was defined as the distance from the cornea to the anterior surface of the IOL at 3 months after surgery plus the distance to the presumed principal object point of the IOLs. The predicted ELP was obtained by a multiobjective evolutionary algorithm and multiple regression analysis, including a dozen parameters, and the difference between the predicted value and measured value (prediction accuracy) was compared between the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the limitations of the ELP in existing formulas, recently, more efforts have been devoted to constructing ELPs that better reflect the true location of the IOL. [5][6][7][8][9] New IOL power prediction methods have also been developed based on the new-generation ELP prediction methods, and they have shown that using a more accurately predicted IOL position helps to improve the IOL power prediction accuracy. 5 It is so far largely unexplored whether inserting a more accurately predicted ELP into existing formulas improves refraction prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%